Pengaruh EPS, PER, dan DER Terhadap Harga Saham Pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia - Seger Priantono; Elok Dwi Vidiyastutik; Yuliati Yuliati (Fakultas Ekonomi Universitas Panca Marga, 2021)
Abstract This research was conducted on 4 cigarette companies listed on the Indonesia Stock Exchange with financial statements in 2013 - 2017 with the aim to determine the influence of Earning Per Share (EPS), Price Earning Ratio (PER) and Debt to Equity Ratio (DER) simultaneously and partially on the share price of Cigarette Companies listed in IDX in 2013 – 2017. This type of research uses causal research. Data is collected by documentation, data analysis methods in the form of multiple linear regression analysis. The results showed that there was a significant influence of EPS, PER and DER simultaneously on the share price, there was a significant influence of EPS partially on the share price, while the variables PER and DER partially had no significant effect on the share price of cigarette companies listed on the Indonesia Stock Exchange (IDX) year 2013 – 2017. Variable EPS that has a dominant effect on the share price with the value of Standardized Coefficients Beta = 0.870. Keyword: EPS, PER, DER, Share Price.